Role Played by Indian Start-Ups in Employment Generation With reference to Start-Ups in Maharashtra (International Journal of Food and Nutritional Sciences, 2022)
India being an underdeveloped country with a large population of employable educated youths,faces severe unemployment situation. The government of India as well as State Governments areconsciously pursuing a policy of supporting of the industrial development and extending all possibleassistance to the industrial sector. Keeping in view this situation it has introduced Start-Ups, Mudra loans,support to self-employment endeavour and the response is very positive